The ring, the gown, and the apple : the role of magical objects in the Byzantine vernacular romance Kallimachos and Chrysorroi - Fonseca, Rui Carlos (2020)
Magical objects play an important role in the fourteenth-century Byzantine vernacular romance "Kallimachos and Chrysorroi", not due to their supernatural powers, but rather in order to make the chivalric status of the romance hero stand out, inasmuch as he does not resort to any of them to achieve his goals.